2006
DOI: 10.1080/13693780500294733
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 defective mice carrying point or null mutations do not show increased susceptibility toCandida albicansin a model of hematogenously disseminated infection

Abstract: We have studied the role of TLR4 in murine defenses against Candida albicans in two TLR4-defective mouse strains: C3H/HeJ mice which have defective TLR4 signaling, and TLR4-/- knockout mice. Both TLR4-defective mice strains experimentally infected with virulent C. albicans cells showed no significant difference in survival as compared with their respective controls. Recruitment of neutrophils to the peritoneal cavity of i.p. infected mice was not affected in TLR4-/-animals, but significantly enhanced in C3H/He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
5
30
0
2
Order By: Relevance
“…TLR4-defective C3H/HeJ mice have been reported to be more susceptible to disseminated candidiasis. 183 Similar results were obtained in models of intragastric infection and intravenous re-infection. 182 However in intravenous infection models, TLR4-/-mice survived longer upon C. albicans hyphae infection, 182 while no difference was observed between the TLR4-/-and wild-type mice upon C. albicans yeasts infection.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micesupporting
confidence: 75%
“…TLR4-defective C3H/HeJ mice have been reported to be more susceptible to disseminated candidiasis. 183 Similar results were obtained in models of intragastric infection and intravenous re-infection. 182 However in intravenous infection models, TLR4-/-mice survived longer upon C. albicans hyphae infection, 182 while no difference was observed between the TLR4-/-and wild-type mice upon C. albicans yeasts infection.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micesupporting
confidence: 75%
“…Total spleen cells were obtained by collagenase D treatment of the organ as previously described [13,14]. Erythrocytes were lysed in ammonium chloride buffer.…”
Section: Detection and Characterization Of Cd451 Transplanted Cellsmentioning
confidence: 99%
“…We have previously described that TLR2 is the major receptor that activates macrophages in response to C. albicans (19,29). Since we found that C. albicans cells inhibit IFN-␥ production by NK cells, we investigated whether TLR2 might be involved in this effect.…”
mentioning
confidence: 99%
“…There is evidence indicating that signal transduction mediated by TLRs is essential for murine resistance to disseminated C. albicans infection, basically through the induction of cytokine and chemokine release (4,11,16,(19)(20)(21)(28)(29)(30).…”
mentioning
confidence: 99%